Answer:
dz = -1.23
[tex]\Delta z[/tex] = -1.2064
Step-by-step explanation:
[tex]z=x^2− x y +8y^2[/tex]
[tex]dz = \frac{\partial z}{\partial x} \; dx + \frac{\partial z}{\partial y} \; dy[/tex]
[tex]\frac{\partial z}{\partial x} = 2x - y[/tex]
[tex]\frac{\partial z}{\partial y} = -x + 16y[/tex]
From (3, −1) to (2.96, −0.95):
[tex]\Delta x = dx = 2.96 - 3 = -0.04[/tex]
[tex]\Delta y = dy = -0.95 - (-1) = 0.05[/tex]
[tex]dz = [2(3) - (-1)] (-0.04) + [-(3) + 16(-1)] (0.05)[/tex]
[tex]dz = -1.23[/tex]
[tex]\Delta z = z(2.96,-0.95) - z(3,-1)[/tex]
[tex]\Delta z = [2.96^2 - 2.96 (-0.95) + 8 (-0.95)^2] - [3^2 - 3 (-1) + 8 (-1)^2][/tex]
[tex]\Delta z = -1.2064[/tex]